Risk factors for myocardial infarction in young women. - Mann, J I (1976)
Seventy-seven women discharged from hospital with a diagnosis of myocardial infarction and 207 control patients were investigated. All were under 45 years of age at the time of admission. Heavy cigarette smoking, reported treatment for pre-eclamptic toxaemia, and type II hyperlipoproteinaemia were found to be independent risk factors for myocardial infarction. Reported treatment for hypertension and diabetes are probably also independently associated with subsequent development of the condition, but the associations between myocardial infarction and reported treatment for obesity and psychiatric illness appear to be secondary. Previous publications have suggested that use of oral contraceptives is an independent risk factor. Examination of the effect of several factors combined, suggests that they act synergistically, the presence of three or more factors increasing the risk 128-fold.